Inside Back Cover: Swelling‐induced Mechanochromism in Multinetwork Polymers (Angew. Chem. Int. Ed. 9/2023). Issue 9 (31st January 2023) - Watabe, Takuma; Otsuka, Hideyuki
Abstract : The swelling force exerted by solvents in polymer gels is revealed to trigger mechanochemical reactions, as reported by Takuma Watabe and Hideyuki Otsuka in their Research Article (e202216469) . A multinetwork strategy based on sequential monomer swelling and polymerization processes makes the original network sensitive to mechanical stimuli. A slight volume expansion caused by swelling leads to the activation of mechanoresponsive linkers in the first network, exhibiting a notable color change.